Hereditary spastic paraplegia associated with thin corpus callosum Paraplegia espástica hereditária associada a hipoplasia de corpo caloso - Hélio A. Ghizoni Teive; Fabio Massaiti Iwamoto; Marcus Vinícius Della Coletta; Carlos Henrique Camargo; Ruth Danielle Bezerra; Guilberto Minguetti; Lineu Cesar Werneck (Arquivos de Neuro-Psiquiatria)
Autosomal recessive hereditary spastic paraplegia (AR-HSP) associated with thin corpus callosum was recently described in Japan, and most families were linked to chromosome 15q13-15. We report two patients from two different Brazilian families with progressive gait disturbance starting at the second decade of life, spastic paraparesis, and mental deterioration. One patient presented cerebellar ataxia. Magnetic resonance imaging (MRI) of the head of both patients showed a thin corpus callosum. AR-HSP with a thin corpus callosum is a rare disorder, mainly described in Japanese patients. We found only 4 Caucasian families with AR-HSP with thin corpus callosum described in the literature. Further studies including additional Caucasian families of AR-HSP with thin corpus callosum are required to delineate the genetic profile of this syndrome in occidental countries. A paraplegia espástica hereditária autossômica recessiva (PEH-AR) associada com hipoplasia de corpo caloso foi inicialmente descrita no Japão. Estudos de ligação genética mostram que a maioria das famílias estão relacionadas ao cromossomo 15q13-15. Relatamos dois pacientes de famílias brasileiras, não relacionadas, com distúrbio de marcha com início na segunda década de vida, paraparesia espástica e comprometimento das funções cognitivas. Um dos pacientes apresentava ataxia cerebelar. A ressonância magnética de encéfalo de ambos os pacientes mostrou hipoplasia de corpo caloso. PEH-AR associada com hipoplasia de corpo caloso é uma condição rara, descrita principalmente em pacientes do Japão. Encontramos apenas 4 famílias caucasianas com PEH-AR e hipoplasia de corpo caloso. Mais estudos com famílias caucasianas são necessários para delinear o perfil genético dessa síndrome em países ocidentais.